2020
DOI: 10.1002/alz.12206
|View full text |Cite
|
Sign up to set email alerts
|

A ketogenic drink improves cognition in mild cognitive impairment: Results of a 6‐month RCT

Abstract: Introduction Counteracting impaired brain glucose metabolism with ketones may improve cognition in mild cognitive impairment (MCI). Methods Cognition, plasma ketone response, and metabolic profile were assessed before and 6 months after supplementation with a ketogenic drink containing medium chain triglyceride (ketogenic medium chain triglyceride [kMCT]; 15 g twice/day; n = 39) or placebo (n = 44). Results Free and cued recall (Trial 1; P = .047), verbal fluency (categories; P = .024), Boston Naming Test (tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
150
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 45 publications
1
150
1
2
Order By: Relevance
“…Ketone salts, MCTs, and at least one ketone ester have been widely studied in humans and shown to be safe and largely well tolerated [ 30 , 31 , 32 ]. Depending on the specific compound, formulation, dose and dosing context, there are some mild-moderate, transient side effects associated with exogenous ketone ingestion; these typically include nausea, dizziness and stomach cramping [ 33 , 34 ], not unlike the transient side-effects sometimes reported by individuals on a ketogenic diet [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ketone salts, MCTs, and at least one ketone ester have been widely studied in humans and shown to be safe and largely well tolerated [ 30 , 31 , 32 ]. Depending on the specific compound, formulation, dose and dosing context, there are some mild-moderate, transient side effects associated with exogenous ketone ingestion; these typically include nausea, dizziness and stomach cramping [ 33 , 34 ], not unlike the transient side-effects sometimes reported by individuals on a ketogenic diet [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blood lipids were also reported-total cholesterol increased by 6% in the kMCT group but remained within the clinical reference range (4.9-5.2 mM). [58]These results provide robust support for the concept that brain energy rescue with ketones can improve cognitive outcomes in both MCI and AD. While further investigations are required to determine the optimal dosage for maximum cognitive benefit of kMCTs, the results of the BENEFIC trial hold promise for future therapeutic treatment with BrainXpert Energy Complex for MCI.…”
Section: Oral Nutritional Supplements For Mild Cognitive Impairment (Benefic Trial)mentioning
confidence: 65%
“…An important part of the energy used by the brain is to maintain information processing speed through impulse propagation [8]. In the BENEFIC trial [13], positive correlations between plasma ketones and tests of episodic memory, executive function and language were found, but not with processing speed. This reinforces the essential role of WM in processing speed, where ketones may act as an important substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results show that WM metabolic deterioration in AD and MCI is specific to glucose and does not involve ketones [10]. Rescuing the brain energy deficit by providing ketones is an emerging therapeutic strategy for aging-associated cognitive decline [11] and has shown promise in several randomized trials [12, 13]. The Brain ENErgy Fitness, Imaging and Cognition (BENEFIC) trial conducted in MCI showed improved measures of episodic memory, language, executive function, and processing speed after the 6-month ketogenic intervention [14] as well as improved cortical energy metabolism.…”
Section: Introductionmentioning
confidence: 99%